2005
DOI: 10.1080/j.0001-6349.2005.00727.x
|View full text |Cite
|
Sign up to set email alerts
|

Arterial embolization and prophylactic catheterization for the treatment for severe obstetric hemorrhage*

Abstract: Arterial embolization is of significant value in treating obstetric hemorrhage. Prophylactic insertion of balloon catheters before cesarean section seems to be a safe and effective method in controlling anticipated bleeding. In patients with persistent bleeding following cesarean section and hysterectomy, embolization could be a primary procedure before re-surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 15 publications
3
47
0
1
Order By: Relevance
“…These life-threatening abnormal placental complications require aggressive blood transfusion therapy and the decision of invasive treatment must be considered within no more than 30 minutes if previous measures have failed22. With today’s imaging capabilities, knowledge of abnormal placentation can lead clinicians to prepare for delivery with interventional radiologists, uterotonics, uterine balloon compression devices, transfusion services, and the optimal surgical team available23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…These life-threatening abnormal placental complications require aggressive blood transfusion therapy and the decision of invasive treatment must be considered within no more than 30 minutes if previous measures have failed22. With today’s imaging capabilities, knowledge of abnormal placentation can lead clinicians to prepare for delivery with interventional radiologists, uterotonics, uterine balloon compression devices, transfusion services, and the optimal surgical team available23, 24.…”
Section: Discussionmentioning
confidence: 99%
“…The extirpative approach usually requires an adjuvant hemostatic technique, such as bilateral internal iliac artery ligation or preoperative placement of balloon occlusion at the upper reaches of the artery. Carnevale et al described 21 cases of IIABO used to treat patients with placenta accreta who underwent cesarean hysterectomy, and concluded that this technique is safe and effectively reduces blood loss.¹ Some reports have reached similar conclusions [24]. In our case, we attempted to perform IIABO; however, massive vaginal bleeding suddenly occurred due to detachment of the placenta as a result uterine contractions.…”
Section: Discussionmentioning
confidence: 53%
“…The generally accepted treatment for placenta percreta is cesarean hysterectomy without attempts to detach the placenta. Preoperative internal iliac artery balloon occlusion (IIABO) has been widely performed to reduce the blood loss during cesarean hysterectomy to treat an abnormal attachment of the placenta [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Hemostasis by interventional radiology is also considered. In obstetric patients, prophylactic arterial embolization and catheterization have been reported [29]. …”
Section: Blood Transfusionmentioning
confidence: 99%
“…Anesthesiologists, surgeons, radiologists, nurses, and clinical engineers in the operating room and staff of blood transfusion services are all essential to save a patient's life [10,11]. The survival rate after massive or critical hemorrhage might be lower in a hospital where surgeons can perform damage control surgery and radiologists can perform interventional radiology [27-29]. Even in JSA-certified training hospitals with more than 500 beds, there are insufficient ABO-identical RBCs to deal with blood loss exceeding 5,000 ml [11].…”
Section: Centralizationmentioning
confidence: 99%